PENGARUH KEPERCAYAAN, KOMITMEN, KOMUNIKASI, PENANGANAN MASALAH DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH BANK MUAMALAT DI SURABAYA - Fitri Ningtyas; Basuki Rachmad (Journal of Business & Banking, 2011)
Customer loyalty is one of the factors influencing the level of sales in a company. Every companyis trying hard to compete so that they can perform various strategies. By doing so, theyare supposed to create their customer loyalty well for each of the goods or services offered.Beside, within this effort, the banks are also doing a lot of strategies to increase their customersloyalty. There are many factors that can affect the loyalty of a customer such as trust,commitment, communication, conflict handling, and customers loyalty. The purpose of thisresearch is to examine the effect of trust, commitment, communication, conflict handling andcustomers satisfaction towards the customers loyalty. This research was conducted in Surabayaexactly on Muamalat Bank. This research uses non probability sampling sample andJudgment sampling to gain 120 bank customers as the respondent. This is conducted bymeans of multiple regressions to analyze the data with SPSS 16.0 for windows. The resultshows that Trust has an effect on Customer Loyalty. Commitment has not any significant effecton Customer Loyalty. Furthermore, communication has not significant effect on CustomerLoyalty, Conflict Handling has not affect on Customer Loyalty, but Customer Satisfactionhas significant effect on Customer Loyalty